(untitled) (Proceedings of The International Conference on Economics and Development, 2017)
The present work is based on survey dataset of 104 investors who invests in various sector of the Indian economy along with IT sector in order to understand the selection process and evaluation criteria of investors towards IT sector in Indian context and to analyze the different dimensions of venture capitalists management and other investors based on risk return aspects, choice of investment firm, expected return on investment and financing mix. Our study gathered importance of selection factor and economic aspects of VCs in the selection process of IT firms and analyze the various other aspects of proposed investment. A designed questionnaire was sent to all investors who are the part of investment process. Factor Analysis and ANOVA has been used to obtain the results.